(untitled) (ADMPG Journal, 2025)
This study aims to analyze the level of disclosure and legibility of socio-environmental information from agricultural cooperatives in Paraná, based on NBC T 15. To this end, a qualitative and quantitative documentary research was carried out on the annual reports, financial statements, explanatory notes and Sustainability Reports for the period from 2018 to 2022. The level of disclosure was assessed through content analysis, while the degree of readability was measured using the Gunning Fog Index. The final sample was made up of 19 cooperatives, listed on the Organization of Cooperatives of the State of Paraná (OCEPAR) portal. The results obtained revealed that there was no significant variation in the socio-environmental disclosure of cooperatives during the period. It was also found that social indicators were more evident in the cooperatives analyzed, and presented a readability index that was considered illegible throughout the period studied by the research. This condition makes it difficult to understand the socio-environmental information disclosed, which can generate users’ lack of interest, proving to be contradictory to the established purposes, which aim at public disclosure and the security that cooperatives are adhering to socio-environmental practices. It was concluded from this work that agricultural cooperatives in Paraná provide insufficient socio-environmental information, most of which are difficult to understand.